Population aging, labor demand, and the structure of wages - Margarita Sapozhnikov; Robert K. Triest (Federal Reserve Bank of Boston, 2007)
One consequence of demographic change is substantial shifts in the age distribution of the working age population. As the baby boom generation ages, the usual historical pattern of there being a high ratio of younger workers relative to older workers is increasingly being replaced by a pattern of there being roughly equal percentages of workers of different ages. One might expect that the increasing relative supply of older workers would lower the wage premium paid for older, more experienced workers. This paper provides strong empirical support for this hypothesis. Econometric estimates imply that the size of one's birth cohort affects wages throughout one's working life, with members of relatively large cohorts (at all stages of their careers) earning a significantly lower wage than members of smaller cohorts. The cohort size effect is of approximately the same magnitude for men and for women. Our results suggest that cohort size effects are quantitatively important and should be incorporated into public policy analyses.
Keywords: J11; J23; J31; 330; Alternde Bevölkerung; Arbeitsnachfrage; Lohnstruktur; USA